INFLUENCE OF QUERCETIN ON BIOCHEMICAL AND MORPHOLOGICAL CHANGES IN RAT TESTES AFTER 30 DAYS LONG CENTRAL DEPRIVATION OF LUTEINIZING HORMONE - Stetsuk, Ye.V.; Shepitko, V.I.; Akimov, O.Ye.; Yakushko, O.S.; Solovyova, N.V. (World of Medicine and Biology, 2021)
Central blockade of luteinizing hormone synthesis by the injection of triptorelin acetate with parallel oral intake of quercetin on the 30th day of the experiment causes minor changes in the structure of the interstitial space of the rats’ testes and is characterized by variability in the populations of interstitial endocrinocytes and macrophages, which in our opinion, affects the change in the parameters of spermatogenesis in the rats’ testes. Quercetin protects tissue of rats’ testes from oxidative damage induced by triptorelin injection on 30th day of the experiment by increasing the antioxidant protection and reducing reactive oxygen species formation. Quercetin increase the arginase-dependent arginine cleavage, which was inhibited by triptorelin injection.
Keywords: testes; interstitial endocrinocytes; macrophages; quercetin; NO synthase; iNOS; cNOS; L-arginine; superoxide dismutase; rats